PENINGKATAN MINAT ANAK USIA DINI MELALUI PEMBELAJARAN AKTIF TK MUARA KASIH KUANTAN SINGINGI - Putri Clawson; Rusni (Jurnal Ta'lim : Journal Ilmu Pendidikan dan Ilmu Keguruan, 2020)
This study aims to determine learning activities in increasing children's interest in drama centers in Muara Kasih Kindergarten, Pucuk Rantau District, Kuantan Singingi Regency. The method used in this research is Classroom Action Research with a total of 20 research subjects consisting of 11 boys and 9 girls. Data collection techniques data collection in this study is observation and documentation. The data analysis technique used in this study is the percentage technique. The results showed that through active learning activities teacher activities in the second cycle showed an increase with a percentage score of 89.6% with good criteria. Increased teacher activity can increase children's activities in Kindergarten Muara Kasih, Pucuk Rantau Subdistrict, Kuantan Singingi Regency, in the second cycle with an average score of 68 or 85% with good criteria. The increase in student activity was followed by an increase in interest in children in Muara Kasih Kindergarten, Pucuk Rantau Subdistrict, Kuantan Singingi District. % with very well developed kiteria (BSB).